2018
DOI: 10.1137/18m1172533
|View full text |Cite
|
Sign up to set email alerts
|

Computation of a Shrinking Interface in a Hele-Shaw Cell

Abstract: The flow in a Hele-Shaw cell with a time-increasing gap poses a unique shrinking interface problem. When the upper plate of the cell is lifted perpendicularly at a prescribed speed, the exterior less viscous fluid penetrates the interior more viscous fluid, which generates complex, time-dependent interfacial patterns through the Saffman-Taylor instability. The pattern formation process sensitively depends on the lifting speed and is still not fully understood. For some lifting speeds, such as linear or exponen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 58 publications
0
31
0
Order By: Relevance
“…Indeed, in Zhao et al. (2018), it was shown that linear theory underpredicts the amplitudes of growing modes in the lifting plate problem.…”
Section: Numerical Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Indeed, in Zhao et al. (2018), it was shown that linear theory underpredicts the amplitudes of growing modes in the lifting plate problem.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…(1997) and Zhao et al. (2018). We consider the interface to be a slightly perturbed circle, where , the perturbation mode is an integer, is the polar angle and is the amplitude of the perturbation.…”
Section: Governing Equationsmentioning
confidence: 96%
See 3 more Smart Citations